2011
DOI: 10.1111/j.1600-0412.2011.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Does exercise during pregnancy prevent postnatal depression?

Abstract: We did not find a lower prevalence of high EPDS scores among women randomized to regular exercise during pregnancy compared with the control group. However, a subgroup of women in the intervention group who did not exercise regularly prior to pregnancy had a reduced risk of postnatal depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 26 publications
2
76
1
4
Order By: Relevance
“…threshold score of 10, 11, 12 and 13). One study 129 reported the number of women who had an EPDS score at two thresholds (i.e. 10 and 13).…”
Section: Statistical Model For Edinburgh Postnatal Depression Scale Tmentioning
confidence: 99%
See 4 more Smart Citations
“…threshold score of 10, 11, 12 and 13). One study 129 reported the number of women who had an EPDS score at two thresholds (i.e. 10 and 13).…”
Section: Statistical Model For Edinburgh Postnatal Depression Scale Tmentioning
confidence: 99%
“…61,121,123,129,[146][147][148][149][150] Yield of systematic reviews Twenty-three reviews were included (i.e. Austin et al, 230 Bennett et al, 231 Cuijpers et al, 68 Dale et al, 232 Dennis and Creedy, 233 Dennis, 234 Dennis, 118 Dennis, 235 Dennis and Kingston, 236 Dennis et al, 237 Dennis, 238 Dodd and Crowther, 239 Fontein-Kuipers et al, 240 Howard et al, 241 Jans et al, 242 Lawrie et al, 243 Leis et al, 244 Lumley et al, 245 Marc et al, 246 Miller et al, 247 Sado et al, 248 Shaw et al 249 and Sockol et al…”
Section: Quantitative Review Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations